Hubungan Perceived Peer Social Support Dan Psychological Well-Being Pada Remaja Awal Dengan Situasi Fatherless Di SMP 3 Payakumbuh - Keno Azizah Rovila; Fauziah Taslim (Science and Education Journal (SICEDU), 2026)
Early adolescents experiencing fatherless conditions are vulnerable to decreased psychological well-being due to the absence of a father figure. This study aimed to examine the relationship between perceived peer social support and psychological well-being among early adolescents with fatherless situations at SMP Negeri 3 Payakumbuh. A quantitative correlational approach was employed, involving 100 early adolescents aged 12–14 years selected through purposive sampling. The instruments used were the Perceived Social Support from Friend (PSS-Fr) scale and Ryff’s Psychological Well-Being (PWB) scale. Data were analyzed using Pearson Product Moment correlation with the assistance of SPSS. The results indicated a significant positive relationship with moderate strength between perceived peer social support and psychological well-being. Most subjects were in the moderate category for both variables. These findings suggest that higher perceived peer social support is associated with higher psychological well-being among fatherless adolescents